Physical and chemical properties of non-exhaust particles generated from wear between pavements and tyres - Alves, C. A. (2022)
A road simulator was used to generate wear particles from the interaction between two tyre brands and a composite pavement. Particle size distributions were monitored using a scanning mobility particle sizer and an aerosol particle sizer. Continuous measurements of particle mass concentrations were also made. Collection of inhalable particles (PM10) was conducted using a high-volume sampler equipped with quartz filters, which were then analysed for organic and elemental carbon, organic constituents and elemental composition. Tyre fragments chopped into tiny chips were also subjected to detailed organic and elemental speciation. The number concentration was dominated by particles <0.5 μm, whereas most of the mass was found in particles >0.5 μm. The emission factor from wear between pavements and tyres was of the order of 2 mg km−1 veh−1. Organic carbon represented about 10% of the PM10 mass, encompassing multiple aliphatic compounds (n-alkanes, alkenes, hopanes, and steranes), PAHs, thiazols, n-alkanols, polyols, some fragrant compounds, sugars, triterpenoids, sterols, phenolic constituents, phthalate plasticisers and several types of acids, among others. The relationship between airborne particulate organic constituents and organic matter in tyre debris is discussed. The detection of compounds that have been extensively used as biomass burning tracers (e.g. retene, dehydroabietic acid and levoglucosan) in both the shredded tiny tyre chips and the wear particles from the interaction between tyres and pavement puts into question their uniqueness as markers of wood combustion. Trace and major elements accounted for about 5% of the mass of the tyre fragments but represented 15–18% of the PM10 from wear, denoting the contribution of mineral elements from the pavement. Sulphur and zinc were abundant constituents in all samples.